Research progress in China on the assessment of cognitive function in schizophrenia - LIU, Dengtang (Editorial Department of the Shanghai Archives of Psychiatry, 2013)
Cognitive impairment – one of the core symptoms of schizophrenia – has become a focus of research about schizophrenia in China and elsewhere. The main reason for the interest in cognitive functioning is that the degree of cognitive impairment is associated both with the current severity of the illness and with the prognosis of the illness due to its effect on individuals' ability to live independently and on their occupational and social functioning. The first study on cognitive function in schizophrenia in China was conducted in the late 1970s; more recently there has been a resurgence of interest in the area because of new information that has emerged as neuroimaging technologies have improved. The current review summarizes studies on cognitive impairment in schizophrenia conducted in China and proposes directions for future research in this area.